Causes of hypogonadotropic hypogonadism predict response to gonadotropin substitution in adults. (18th January 2016) - Rohayem, J.; Sinthofen, N.; Nieschlag, E.; Kliesch, S.; Zitzmann, M.
Summary: Germ cell and Sertoli cell proliferation and maturation in human testes occur in three main waves, during the late fetal and early neonatal period and at early puberty. They are triggered by periods of increased activity of the hypothalamic‐pituitary‐gonadal (HPG) axis. In hypogonadotropic hypogonadism (HH), these processes are variably disturbed. The objective of this study was to explore whether success of gonadotropin replacement in HH men is predictable by the origin of HH, indicating time of onset and severity of GnRH/gonadotropin deficiency. The data of 51 adult HH patients who had undergone one cycle of hCG/FSH treatment were reviewed. Five groups were established, according to the underlying HH origin. Therapeutic success by final bi‐testicular volumes (BTVs) final sperm concentrations (SC) and conception rates were compared and related to baseline parameters, indicative of the degree of HPG‐axis disruption. Overall, BTVs rose from 13 ± 15 to 27 ± 15 mL, spermatogenesis was induced in 98%, with mean SCs of 15 ± 30 mill/mL, spontaneous pregnancies in 37% and additional 18% via intracytoplasmic sperm injection. Kallmann syndrome patients had the poorest responses (BTV: 16.9 ± 10 mL; SC: 3.5 ± 5.6 mill/mL), followed by patients with congenital/infancy‐acquired multiple pituitary hormone deficiencies (MPHD) and patients with HH+absent puberty (BTV: 21 ± 14/24 ± 9 mL; SC: 5.5 ± 6.5/ 14.5 ± 23.8 mill/mL). HH men with pubertal arrest and with post‐pubertally acquired MPHD had the best results (BTV: 36 ± 14/38 ± 16 mL; SC: 25.4 ± 34.2/29.9 ± 50.5 mill/mL). Earlier conception after 20.3 ± 11.5 months (vs. 43.1 ± 43.8; p = 0.047) of gonadotropin treatment with higher pregnancy rates (62% vs. 42%) was achieved in the two post‐pubertally acquired HH subgroups, compared to the three pre‐pubertally acquired. Therapeutic success was higher in patients without previously undescended testes, with higher baseline BTVs (pre‐ vs. post‐pubertal HH: 5 ± 4 mL vs. 26 ± 16 mL; p < 0.0001) and higher baseline inhibinB levels (pre‐ vs. post‐pubertal HH: 16.6 vs. 144.5 pg/mL; p = 0.0004). The cause of HH is a valuable predictor of outcome of gonadotropin replacement in adults.